Loss of CB1 receptors leads to differential age-related changes in reward-driven learning and memory - Albayram, Onder; Bilkei-Gorzo, Andras; Zimmer, Andreas (Frontiers in Aging Neuroscience, 2012)
Previous studies have shown that cannabinoid 1 (CB1) receptor signaling dissociates between reward-associated and aversive memories. The influence of CB1 receptors on the aversion-driven spatial learning in the Morris water maze test is strongly age-dependent: mice with genetic deletion of CB1 receptors (Cnr1-/-) show superior learning when young but inferior learning when old compared to age-matched wild-type mice. Whether the reward-driven spatial learning is influenced in the same way by CB1 receptor signalling as the aversion-driven learning remains unclear. Thus, we examined the performance of Cn1-/- and their wild-type littermates at ages of 2-, 5-, and 12-month-old in the 8-arm radial maze test - a reward-motivated model of spatial learning. Interestingly, 2-month-old Cnr1-/- mice had a superior learning ability to wild-type mice. At the age of 5-months, Cnr1-/- mice showed the same performance as the wild type littermates. However, 12-month-old Cnr1-/- mice showed significantly impaired performances in each parameter of the test. Accordingly, this study provides compelling support for our previous result that genetic deletion of CB1 receptor leads to early onset of age-related memory decline, similarly affecting both reward and aversion-driven learning.